PERAN PENGHUBUNG KOMISI YUDISIAL DALAM MENJAGA DAN MENEGAKKAN KEHORMATAN, KELUHURAN MARTABAT, SERTA PERILAKU HAKIM DI JAWA TENGAH - Setyaputra, Kurnia; Suranto, Suranto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This study aims to determine the role of the Central Java Liaison of Judicial Commission in maintaining and upholding the honor, the nobleness of dignity and behavior of judges in Central Java. The research method used in compiling this legal research is descriptive and non-doctrinal research in legal research. This research approach uses a qualitative approach and the object of this research is the Central Java Liaison of the Judicial Commission located in Semarang which was conducted by interviews and observations. Based on the results of research and explanation, the conclusion is that the Liaison of the Central Java Judicial Commission has 3 (three) main tasks and 2 (two) additional tasks. The Liaison of Judicial Commission in maintaining and upholding the honor, the nobleness of dignity and behavior of judges in Central Java is in accordance with Judicial Commission Regulation Number 1 of 2017 concerning Formation, Arrangement, and Procedures of Liaison of Judicial Commissions in the Regions.